2020
DOI: 10.1155/2020/8851030
|View full text |Cite
|
Sign up to set email alerts
|

Fresh and Hardened Properties of Concrete Incorporating Binary Blend of Metakaolin and Ground Granulated Blast Furnace Slag as Supplementary Cementitious Material

Abstract: The growing demand for cement has created a significant impact on the environment. Cement production requires huge energy consumptions; however, Pakistan is currently facing a severe energy crisis. Researchers are therefore engaged with the introduction of agricultural/industrial waste materials with cementitious properties to reduce not only cement production but also energy consumption, as well as helping protect the environment. This research aims to investigate the influence of binary cementitious material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 30 publications
6
26
0
Order By: Relevance
“…It was observed that the flexural strength was enhanced while utilizing jute fiber up to 0.50% and WSA equal to 30% together in concrete. is opinion was in agreement with that of Bheel et al [45] that the flexural strength was enhanced as the extent of metakaolin and GGBFS equal to 10% as the binary cementitious component in concrete improved.…”
Section: Flexural Strengthsupporting
confidence: 92%
See 2 more Smart Citations
“…It was observed that the flexural strength was enhanced while utilizing jute fiber up to 0.50% and WSA equal to 30% together in concrete. is opinion was in agreement with that of Bheel et al [45] that the flexural strength was enhanced as the extent of metakaolin and GGBFS equal to 10% as the binary cementitious component in concrete improved.…”
Section: Flexural Strengthsupporting
confidence: 92%
“…It was observed that the permeability of concrete was reduced while jute fiber and WSA utilized increase together in concrete. is opinion conforms with that of Bheel et al [45] that the permeability of concrete was reduced as the extent of metakaolin and GGBFS as the binary cementitious component in concrete increases.…”
Section: Modulus Of Elasticitysupporting
confidence: 91%
See 1 more Smart Citation
“…Portland cement (PC) is a raw construction material that is currently consumed in huge quantities (approximately 4.0 billion tons annually), and by 2030, its global production is projected to be approximately 5.5 billion tons [1,2]. e expeditious infrastructure growth in Asia, Middle East, and other developing regions in the world is expected to increase the demand for cement and concrete products [3].…”
Section: Introductionmentioning
confidence: 99%
“…Silica fume (SF), fly ash (FA), metakaolin (MK), and a broad series of NPs are regularly used as SCMs in concrete production. With regard to pozzolanic reactivity, the finer the SCM particles ( ≤ 75 μm) are, the more favorable the cement response is [2,3]. erefore, SF is probably the preferred SCM owing to its superfine particles and, consequently, its significant pozzolanic activity.…”
Section: Introductionmentioning
confidence: 99%